Pemberian Rebusan Jahe dan Daun Pepermint Efektif dalam Pencegahan Nausea Pada Pasien Post Operasi dengan Anastesi Spinal di Ruang Bedah: Giving Decoction of Ginger and Peppermint Leaves is Effective in Prevention of Nausea in Postoperative Patients with Spinal Anesthesia in the Operating Room - Mustopa Mustopa (Jurnal Interprofesi Kesehatan Indonesia, 2022)
Introduction: Spinal anesthesia can cause symptoms of pain, nausea, and vomiting that often occur in 80% of patients after anesthesia and surgery. Due to suture damage, regurgitation, aspiration, electrolyte balance, and dehydration if Post Operative Nausea Vomiting (PONV) is not treated and is a major concern in postoperative care. Nausea and vomiting are frequent complications of spinal anesthesia, with an incidence of 20-40%. Objectives: To compare the effect of boiled ginger and boiled peppermint in reducing the level of nausea and vomiting. Method: The type of research used in this study is a quasi-experiment with a Nonequivalent Control Group Design. Respondents in this study amounted to 15 people. Result: There was a decrease in the intensity of nausea and vomiting after being given ginger and/or peppermint decoction with the same effectiveness. The results of the Mann-Whitney U Test statistical test obtained a significance value of p-value = 0.472 < from 0.005. Conclusion:. There is a significant effect between ginger and peppermint decoction in reducing the level of nausea and vomiting in spinal anesthesia post-op patients in the operating room of the Bogor City Hospital with the same effectiveness value.